Structural Reforms and Firms' Productivity : Evidence from Developing Countries - Kouame, Wilfried A.; Tapsoba, Sampawende J.-A. (World Bank, Washington, DC, 2018)
This paper assesses the effects of selected structural reforms on labor productivity growth for 37 developing countries over 2006-14. It combines newly constructed reform indexes using the International Monetary Fund's Monitoring of Fund Arrangements data set and firm-level productivity from the World Bank Enterprise Surveys. The paper highlights the following results. Structural reforms under consideration in this study -- financial, fiscal, real sector, and trade reforms -- significantly improve productivity at the firm level. Interestingly, real sector reforms have the most sizable effects on firms' productivity. The relationship between reforms and productivity is nonlinear and shaped by certain characteristics of firms, including financial access, a distortionary environment, and firms' size. The pace of reforms matters, since being a “strong reformer” is associated with a clear productivity dividend for firms. Finally, except for financial and trade reforms, all the macroeconomic reforms considered are bilaterally complementary in improving firms' productivity. These findings are robust to several sensitivity checks, including alternative methodologies and measures of productivity, and a counterfactual experiment based on unsuccessful reforms.